Development of Mobile Gamified Interface for Japanese Language Learning through Design Thinking - Hardy Padmayudha Nugraha; Dedi Kuswandi; Agus Wedi (JoEICT (Jurnal of Education And ICT), 2025)
Learning Japanese scripts such as hiragana and katakana often present significant challenges for beginners due to the similarity in character shapes, the large number of characters to memorize, complex stroke orders, and the limited use of engaging and interactive learning media. Without proper learning strategies and tools, learners may quickly lose motivation and face difficulties in mastering these basic writing systems. This study aims to design the interface of a mobile-based gamified learning platform intended to increase learner motivation and improve the overall effectiveness of the learning process. The Design Thinking methodology was employed to gain in-depth insights into user needs, involving five iterative stages: empathize, define, ideate, prototype, and test. The resulting interface integrates gamification elements such as points, badges, levels, and quests to create a more engaging user experience. Usability testing conducted using the System Usability Scale (SUS) produced an average score of 82.5, which falls under the “excellent” category with a letter grade of B. These findings suggest that the developed interface is intuitive, easy to use, and well-received by users.